2013
DOI: 10.1186/1748-717x-8-222
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated stereotactic radiation therapy for recurrent glioblastoma: single institutional experience

Abstract: BackgroundGlioblastoma (GBM) is the most common malignant primary brain tumor in adults. Tumor control and survival have improved with the use of radiotherapy (RT) plus concomitant and adjuvant chemotherapy, but the prognosis remain poor. In most cases the recurrence occurs within 7–9 months after primary treatment. Currently, many approaches are available for the salvage treatment of patients with recurrent GBM, including resection, re-irradiation or systemic agents, but no standard of care exists.MethodsWe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 72 publications
2
19
1
Order By: Relevance
“…It was ultimately decided that patients with poor prognosis with limited salvage treatment options would be selected. The median KPS of patients receiving re-RT with HT was 60, lower than that in previous studies [25,27]. Furthermore, we did not compare the combination of RT and HT with RT alone.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…It was ultimately decided that patients with poor prognosis with limited salvage treatment options would be selected. The median KPS of patients receiving re-RT with HT was 60, lower than that in previous studies [25,27]. Furthermore, we did not compare the combination of RT and HT with RT alone.…”
Section: Discussioncontrasting
confidence: 44%
“…In another study, patients receiving RT with 30 Gy in 5 fractions had a median OS of 7.9 months after re-RT [24]. Ciamella et al found that the median OS was 9.5 months in a HFSRT study with 25 Gy administered in 5 fractions [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest incidence (36%) was reported by the Royal Marsden experience, where 36 patients with recurrent GBM (median tumor volume 24 cm 3 ) were treated with doses ranging from 20 -50 Gy in 5-Gy per fraction [17]. Following a fractionation scheme of 25 Gy/5 fractions, Ciammella, et al [11] reported neurological deterioration reversible with dexamethasone in 13% of patients. Another study using a median dose of 37.5 Gy/15 fractions in 25 patients reported clinical necrosis in one patient and cranial nerve palsy in another patient [10].…”
Section: Discussionmentioning
confidence: 91%
“…Of these, HFSRT has emerged as a noninvasive method to deliver a high dose of radiation to the tumor site. In the treatment of recurrent GBM, numerous studies have documented a survival advantage on the use of HFSRT [10][11][12][13][14][15][16][17][18] and HFSRT in combination with chemotherapy [19][20][21][22][23][24]. Specifically, Iuchi, et al [25] has shown that a single dose of more than 20 Gy is able to achieve durable local control in 72% of patients; however, radiation necrosis (RN) was observed in 43% of patients.…”
Section: Introductionmentioning
confidence: 99%